The 1775 Agenda of Gottfried Ostermeyer: The Last Specifically Lutheran Lithuanian Liturgical Book in the Prussian Kingdom - Petkūnas, Darius (Senoji Lietuvos literatūra, 2016)
Up to 1730 Prussian Lithuanian Lutheran pastors used manuscript agendas or liturgical texts published in hymnals and catechisms. These texts were translated from the German-language Prussian agendas printed in 1544, 1558, and 1568. In 1549 Martynas Mažvydas (Martin Moswidius) published his first rhythmic setting of the Ambrosian hymn ‘Te Deum laudamus’, and in 1559 he published the form for Holy Baptism, Forma Chrikstima. The most important of his liturgical works was the two-volume hymnal Gesmes Chriksczoniskas (Christian Hymns) which appeared in 1566 and 1570. Both volumes were published by Baltramiejus Vilentas (Bartholomäus Willentus). It included such parts of the Divine Service as the Introits, ‘Kyrie’, ‘Gloria in excelsis’ with ‘Laudamus’, versicles and responses, collects, sequences, a versified setting of the Nicene Creed, the Litany, and other liturgical materials needed for the Lutheran Mass, Matins, and Vespers. All that was lacking was the Liturgy of the Sacrament, which in Prussia included a Paraphrase of the Our Father, an Exhortation to communicants, the Consecratory Words of Christ over the bread and wine, the Collect of Thanksgiving, and the final Benediction. Mažvydas had translated this setting into Lithuanian as well, but it did not appear in print until 1589 when it was published by Jonas Bretkūnas (Johann Bretke) in his hymnal Giesmes Duchaunas (Spiritual Hymns). In 1579 Baltramiejus Vilentas published the Enchiridion, i. e., Luther’s Small Catechism, which included Luther’s forms for Marriage and Baptism. That same year, 1579, he published in Lithuanian a book of pericopes, Euangelias bei Epistolas (Gospels and Epistles), which included readings for every Sunday and feast day. It was through the contributions of Mažvydas and his co-workers that the Lithuanian language became a liturgical language, an officially recognized language throughout the duchy. It contributed to the national identity and made it possible for the Lithuanian language to escape the fate of the ethnic Prussian language which fell by the wayside in the sixteenth–seventeenth centuries through forced Germanization. New editions of these liturgical texts were published in the hymnals of 1589, 1612, 1666, 1685, and 1705. In 1625 Jonas Rėza (Johann Rehsa) published the first Lithuanian Psalter. Jonas Bretkūnas had translated the Psalter into Lithuanian in 1580, but it was never published. The Rhesa volume used the Bretkūnas text, and was subsequently reprinted in 1728, 1740, and 1749. It was also included in the 1735 and 1755 editions of the Lithuanian Bible. The forms for Baptism, Marriage, and the Sacrament of the Altar were republished in a new edition of ‘Lysius Catechism’, printed in 1722 by Gabrielius Engelis (Gabriel Engel). It was not until 1730 that the first official Agenda of the Prussian Lithuanian Church was published. It was printed in Königsberg under the title: Dawádnas Pamokinnimas kaipo wissi, Lietuwoje, po Maloningiáusio Prusû Karalum’ essantieji Kunningai, kaip Diewo Tarnai tur elgtis, noredami ßwentą Klebonû Urėdą wiernay ißpildit (A Thorough Instruction Concerning how All Pastors in Lithuania Under the Most Gracious King of Prussia Should Conduct Themselves as Servants of God in the Proper Fulfilment of Their Pastoral Duties). The book contained forms for Holy Baptism, the Lord’s Supper, Holy Matrimony, Confirmation, apublicprayerforcommunicants, and especiallyreconciled public penitents, together with an admonition ‘that they be joyfully received back into the fellowship of the church.’ Also included were forms for the installation of a parish pastor, general prayers of the church, special prayers for the high feasts, seasonal collects, together with versicles and responses, and a six-part History of the Passion of Christ. In this agenda the Liturgy of the Word was not printed, as it should have been; only the Lord’s Supper liturgy was published. The Liturgy of the Sacrament differed little from that found in the 1568 Agenda. Lacking, however, was any clear guidance about how the liturgy was to be performed and what hymns were to be sung during Communion. The liturgical terminology was also altered and the word ‘Mass’ was dropped as a term designated the Divine Liturgy. The word ‘Mass’ came to refer only to the sermon. It also appears that the Lord’s Supper was no longer celebrated every Sunday in every church. Now most of the Sunday services were without Holy Communion. Pietism had spread throughout the Church and the sermon was now considered the most important element to the worshipers. As the Word was now separated from and elevated above the Sacrament, so, too, the pulpit came to be elevated above the altar, not only figuratively but architecturally as well. The initiative to produce a new edition of the agenda was taken by Gottfried Ostermeyer of Trempen (Lith. Trempai). He could give two important reasons for his decision to do so. First, the 1730 agenda lacked the necessary forms for the public recognition of an Emergency Baptism and the Communion of the Sick. In addition, Ostermeyer was convinced that the text of the agenda was in need of both grammatical and stylistic improvement. His new agenda appeared in 1775. It was published in Königsberg under a new title: Agenda tattai esti Suráßimas Pagraudinnimû ir Maldû, Lietuwôs Baźnyćiosa skaitomû nůg Kunnigû ßwentus sawo Urėdo Darbus pilnawojanćiujû (Agenda, that is, a Collection of Exhortations and Prayers Read in the Lithuanian Churches by Parish Pastors in the Exercise of Their Holy Duties). Included were the forms for the Installation of a Pastor into the parochial ministry, the Holy Baptism, the recognition of Emergency Baptism, Confirmation, the Reconciliation of manifest sinners, the Lord’s Supper, the Communion of the Infirm, Marriage, and selected collects. Missing from this edition was the History of the Passion, because from 1732 it had been included in the hymnals. Shortly after this Agenda was published, Ostermeyer became deeply involved in a debate with Kristijonas Gotlybas Milkus (Christian Gottlieb Mielcke) concerning the proper Lithuanian terminology to be used in the hymnal. Ostermeyer contended that although the word ‘body’ was usually rendered in Lithuanian as ‘kūnas’, it would have been more proper to use the word ‘flesh’ (‘mėsa’), a word which most commonly referred to meat. In the Words of Consecration and in the distribution formula, he perpetuated the usage of the old 1730 translation ‘body’ (‘kūnas’), but in the marriage rite description of the creation of Eve, when God removed a rib from Adam and filled up the place with ‘body’, Ostermeyer parenthetically added ‘flesh’. Thirteen years later, in 1788, Kristijonas Gotlybas Milkus referred to this parenthetical remark by Ostermeyer, saying that it clearly showed his incompetence as a linguistic scholar, for ‘he turned Adam’s body into a carcass’. Milkus claimed the support of the avowed literary expert Pastor Kristijonas Donelaitis (Christian Donalitius) of Tollmingkehmen (Lith. Tolminkiemis) in support of his contention and went on to say that a number of his colleagues in the priesthood silently marvelled that a man ‘so linguistically incompetent should dare to correct the Agenda’. Despite all these critical remarks, Prussian Lithuanian priests made great use of the ‘Ostermeyer’s Agenda’. Ostermeyer himself called it an ‘Improved Agenda’. In fact, the text of the agenda was now clearer and the book included several necessary forms for pastoral use as well. This was to be the last printed specifically Lutheran agenda in the Lithuanian language exhibiting old Reformation forms from the Ducal Prussian liturgical tradition. This Lutheran liturgical tradition ended abruptly when Prussian King Friedrich Wilhelm III introduced a Union Agenda of his own composition to be used by both the Lutherans and the Reformed. The new agenda for the Province of [East and West] Prussia was translated into Lithuanian in 1825 by Martynas Liudvikas Rėza (Martin Ludwig Rhesa) and published in its final form in 1830.